Digital Transformation in Acquisition: Using Modeling and Simulation to Advance the State of Practice. Issue 1 (26th September 2022) - Hutchison, Nicole; Tao, Hoong Yan See; Clifford, Megan; Burley, Camryn; Arndt, Craig; Wach, Paul; Sherburne, Tim; Beling, Peter; McDermott, Tom; Blackburn, Mark; Long, David; Verma, Dinesh
Abstract: Digital transformation is a key enabler for successful acquisition and sustainment in a rapidly changing environment of increasing threats and challenges. This paper provides an overview of digital transformation in acquisition and ongoing relevant work that contributes to the development of training for the US Department of Defense (DoD) acquisition workforce. One of the main contributions is the development of models and simulations for training purposes. The team researched on current uses of modeling and simulation before proposing models and simulations ("case studies") that could be incorporated in the training materials at the Defense Acquisition University (DAU) and extend applicability beyond the DoD to contribute to the DE body of knowledge and DE community. The acquisition workforce must undergo significant transformation, which is not an easy transition, to overcome the challenges of digital transformation. Cultural change is an important shift that will have to happen in the workforce to enable digital transformation. This paper highlights the three‐pronged approach for competency identification to support competency development. The research is centered on improving the acquisition workforce's ability to support Digital Acquisition through the identification of critical competencies for individuals, and for program offices and the development of models and simulation in the DAU curriculum to enable effective digital transformation.